Bridge's piers damage subjected to multiple earthquakes: Markov model vs Regression model - Turchetti,F; Tubaldi,E; Patelli,E; Castaldo,P; Di,Pilato D; Malaga,Chuquitaype C (2022)
Recently developed methodologies based on a probabilistic seismic demand model (PSDM) and based on a Markovian model for the prediction of damage accumulation in structures subjected to multiple earthquakes within their lifetime are compared. A stochastic earthquake hazard model is used for generating sample sequences of ground motion records providing the reference solution and then used to estimate the probabilistic distribution of the damage accumulated during the time interval of interest. Besides evaluating the effectiveness of each approach, possible improvements of the cumulative demand model are tested. A reinforced concrete bridge model with a single pier is examined as case study and Park-Ang damage index is considered to describe the damage accumulation. The results demonstrate the importance of considering the occurrence of multiple shocks.